Improvements in Forestry Training with Particular Reference to India - Stracey, P. D. (Indian Forester, 1961)
The method of training for forestry are not the same all over the world. In Europe and America, it is customary for this training to be included as one of the University courses, a degree in forestry from a recognised college being a pre-requisite for entrance to the forest service of a country. The colonical forest departments, particularly those of the British Commonwealth, have developed along somewhat different lines. India, which has a forest administration dating back nearly one hundred years, early developed local training institutions for the requirements of her State Forest Departments. The probationers for the superior forest posts were trained in Europe in the past. Other colonical countries worked on more or less the same pattern and the system has been found suitable for the requirements of such countries. In India, there has been a great expansion of forestry and consequently an increase in the demands for more trained personnel. This paper contains a brief account of the system of training in India and offers suggestions for improved methods of training which will help to maintain the standards of forestry education, while coping with the greatly increased demands for trained personnel.